IMPROVING STUDENTS’ READING COMPREHENSION THROUGH RECIPROCAL TEACHING STRATEGY ON REPORT TEXT - Elisa Yulianti; Eko Setiawan (IKIP Siliwangi, 2019)
The objective of this research is to know how to use of reciprocal methods to teaching reading comprehension of the senior high school in second grade. The background of the research is to help students’ to cope the difficulties in reading report text, because there are still many students who find it difficult to read English and the lack of reading comprehension of students in class XI Animation of SMK TI Garuda Nusantara Cimahi with the aim to know whether there is an increase in student scores after using the Reciprocal Learning method. The author uses the reciprocal method to increase the ability of students to read comprehension. This research is quantitative by using experimental research methods. After conducting the research obtained the data pre-test (80) and post-test (95). Based on these data, it can be concluded that the use of reciprocal methods in the report text material can improve reading comprehension in students of class XI Animation 2 Vocational School of TI Garuda Nusantara Cimahi.